Attention capture by salient object groupings in the neglected visual field. (May 2021) - Nowack, Leonie; Finke, Kathrin; Biel, Anna Lena; Keller, Ingo; Müller, Hermann J.; Conci, Markus
Abstract: The integration of fragmentary parts into coherent whole objects has been proposed either to rely on the availability of attentional resources or to arise automatically, that is, from preattentive processing (prior to the engagement of selective attention). In the present study, these two alternative accounts were tested in a group of neglect patients with right-hemisphere parietal brain damage and associated deficits of selective attention in the left (visual) hemispace. The reported experiment employed a search task that required detection of targets in the left and/or right hemifields, which were embedded in configurations that consisted of variants of Kanizsa figures. The results showed that a salient, grouped Kanizsa triangle presented within the unattended, left hemifield can substantially improve contralesional target detection, though the very same triangle configuration does not facilitate target detection in the impaired hemifield when presented together with an ipsilesional, but non-salient (i.e., structurally non-integrated, isolated) target. That is, attention is captured by the grouped object in the impaired hemispace only when it is not engaged in the processing of an (isolated) object in the attended hemispace. This demonstrates that both part-to-whole-object integration and search guidance by salient, integrated objects crucially require attentional resources.